2021
DOI: 10.3389/fped.2021.690333
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Test for Respiratory and Asthma Control in Kids Initial Score on the Prognosis of Pre-school Children With Asthma: A Prospective Cohort Study

Abstract: Objective: The test for respiratory and asthma control in kids (TRACK) is currently the only standard follow-up tool for children under 5 years of age with asthma. The purpose of this study was to investigate the relationship between the TRACK initial score (Ti) and their prognosis after 6 months of follow-up in pre-schoolers with asthma.Design: A prospective cohort study.Methods: The study included pre-schoolers diagnosed with asthma at the Shanghai Children's Medical Center between January 2019 and June 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Similarly, the distribution of TRACK score values in our patient population highlighted a mean value of 68.3 ± 20.8, confirming the poor control of the symptoms of these patients and supporting the diagnostic suspicion of asthma 54 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, the distribution of TRACK score values in our patient population highlighted a mean value of 68.3 ± 20.8, confirming the poor control of the symptoms of these patients and supporting the diagnostic suspicion of asthma 54 …”
Section: Discussionsupporting
confidence: 76%
“…53 Similarly, the distribution of TRACK score values in our patient population highlighted a mean value of 68.3 ± 20.8, confirming the poor control of the symptoms of these patients and supporting the diagnostic suspicion of asthma. 54 Regarding to the optimal cut-offs for establishing a positive BDR with IOS in preschool children, we found that a decrease in R5 of 25.7% and an increase in X5 of 25.7% on baseline exhibited the best combination of sensitivity and specificity to detect an increase of FEV 1 ≥ 12% and/or ≥200 mL with an AUC of 0.77 and 0.75, respectively. respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The nurses were advised to seek medical attention promptly if any discomfort was observed. The TRACK scale is an evaluation tool for the control of childhood asthma developed by the American scholar Murphy[ 7 ]. It is currently the only tool to evaluate the level of asthma control in children aged less than five years as well as the first evaluation tool that includes damage and risk.…”
Section: Methodsmentioning
confidence: 99%